Cross-cultural learning challenges and teaching strategies for first-year Asian students in Australian universities - Xiao, J.; Lu, J.; Chin, Kum; Xu, J.; Yao, J. (INSTICC - Institute for systems and technologies of information, control and communication, 2010)
With the dramatic increase in the number of Asian students in the past few years, the cross-cultural teaching and learning situation becomes an important issue in Australian universities. To tickle this issue, we conducted a survey to students studying Information Technology and Business courses in five Australian universities. A total of 639 international students and 387 local students completed the questionnaire survey. Our survey results revealed a number of leaning challenges facing international students, especially first year Asian students. Student and staff interviews were also conducted to discover further facts that may not be covered by the questionnaire, and to check whether or not the survey (and interview) results represent the similar view from the staff side. The initial interview outcome, based on an incomplete number of interviews, generally supported the findings from the student survey. This paper is to examine the challenges, especially those from language and cultural aspects that face Asian students studying in Australian universities, and summarize some responses to relevant survey/interview questions from both local and international students. Some teaching strategies on how to improve language ability and classroom skills for first-year Asian international students are initiated.